2017
DOI: 10.1186/s12872-017-0678-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in primary and secondary prevention of cardiovascular risk in the continental and Mediterranean regions of Croatia

Abstract: BackgroundThe aim of this observational study was to evaluate the effect of Mediterranean and continental nutrition on cardiovascular risk in patients with acute and chronic coronary heart disease in Croatia.MethodsThe study included 1284 patients who were hospitalized in a 28-month period due to acute or chronic ischaemic heart disease in hospitals across Croatia. An individual questionnaire was prepared which enabled recording of various cardiovascular risk factors.ResultsPatients with chronic coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is worthy to mention that high proportion of participants had recommended daily olive oil and weekly fish intake and those MD foods are recognized in preventing CVD risks [ 3 ]. The study done on 1284 hospitalized patients due to acute or chronic ischemic heart disease in hospitals across Croatia showed that patients with chronic heart disease had more MD habits, concluding that MD is associated with reduced risk of developing cardiovascular disease [ 28 ]. Those participants with unfavorable lipid profile had lower adherence to MD and lifestyle, which expose them more to CVD risk, and our results are similar to the results of lipid profile of Spanish workers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy to mention that high proportion of participants had recommended daily olive oil and weekly fish intake and those MD foods are recognized in preventing CVD risks [ 3 ]. The study done on 1284 hospitalized patients due to acute or chronic ischemic heart disease in hospitals across Croatia showed that patients with chronic heart disease had more MD habits, concluding that MD is associated with reduced risk of developing cardiovascular disease [ 28 ]. Those participants with unfavorable lipid profile had lower adherence to MD and lifestyle, which expose them more to CVD risk, and our results are similar to the results of lipid profile of Spanish workers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational prospective population-based cohort study including 23,232 men and women, Paterson et al (2018) reported that subjects adhering to a Mediterranean diet had a lower risk of stroke [ 107 ]. In an observational study including 1284 patients hospitalized for an acute or chronic ischemic heart disease Siki et al (2017) reported similar reductions in risk [ 108 ]. Based on the analysis of data from the National Nutrition and Physical Activity Survey, including 9435 subjects, Aridi et al reported that higher adherence to a Mediterranean diet decreased the incidence of CDs, with lower concentrations of total cholesterol, low-density lipoprotein, diastolic blood pressure and dyslipidemia [ 109 ].…”
Section: Link Between Nutrition Periodontitis and Other Main Chromentioning
confidence: 99%
“…These findings are important since it has been observed that dietary behavior has a beneficial impact both on general health 41 and cardiovascular health. 42,43 In addition, there was an increase in the proportion of patients considered highly adherent to the Mediterranean diet post-test in both subgroups. Whereas the Mediterranean diet has been indicated as one of the healthiest eating patterns, 44 the high adherence to the diet by post-test patients could be a reflection of the educational process, since education can influence patients' food choices.…”
Section: Discussionmentioning
confidence: 91%